2022
DOI: 10.3390/robotics11060140
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Printing of Cylindrical Nozzle Elements of Bernoulli Gripping Devices for Industrial Robots

Abstract: The application of additive technologies, namely, fused deposition modeling, is a new reality for prototyping gripping devices of industrial robots. However, during 3D printing of holes and nozzle elements, difficulties arise with reducing their diameter. Therefore, this article conducts a comprehensive study of the Bernoulli gripping device prototype with a cylindrical nozzle, manufactured by fused deposition modeling 3D printing. The three main reasons for reducing the diameter of the gripper nozzle after pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 91 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…On further analysis of the experimental data, when only the nozzle diameters of 0.4 mm, 0.6 mm and 0.8 mm were varied and the other factors were kept constant (same material, same sample thickness and same internal configuration), it was concluded that about 80% of the maximum absorption coefficient values were obtained with the 0.4 mm nozzle diameter and 20% of the maximum values were obtained for the 0.6 mm nozzle diameter. Thus, it can be stated that another important aspect regarding the FFF process was the correct choice of the deposition layer height (0.2 mm), which is recommended to not exceed the print nozzle diameter (0.4 mm) in order to obtain good mechanical and acoustic performance [49][50][51]. Figure 5 plots the influence of the sound transmission loss (STL) as a function of the 3D-printed sample.…”
Section: Influence Of Nozzle Diameter On Acoustic Performance Of 3d-p...mentioning
confidence: 99%
“…On further analysis of the experimental data, when only the nozzle diameters of 0.4 mm, 0.6 mm and 0.8 mm were varied and the other factors were kept constant (same material, same sample thickness and same internal configuration), it was concluded that about 80% of the maximum absorption coefficient values were obtained with the 0.4 mm nozzle diameter and 20% of the maximum values were obtained for the 0.6 mm nozzle diameter. Thus, it can be stated that another important aspect regarding the FFF process was the correct choice of the deposition layer height (0.2 mm), which is recommended to not exceed the print nozzle diameter (0.4 mm) in order to obtain good mechanical and acoustic performance [49][50][51]. Figure 5 plots the influence of the sound transmission loss (STL) as a function of the 3D-printed sample.…”
Section: Influence Of Nozzle Diameter On Acoustic Performance Of 3d-p...mentioning
confidence: 99%
“…The influence of the input parameters of jet capture devices on their power and energy characteristics is substantiated in the paper [43]. The authors developed a method of designing a cylindrical nozzle for prototyping Bernoulli gripping devices by the 3D printing method [44] and investigated the influence of 3D printing parameters on the power characteristics of the gripping device. Furthermore, the authors in papers [45] address the pressing matter of reducing energy usage in object manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that BGDs exhibit high dynamic characteristics, enabling contactless manipulation of objects [45,46]. The process of manufacturing and prototyping Bernoulli traps also has an important effect on their technical characteristics, which is explored in paper [51]. Most of the scientific papers [47][48][49][50] are dedicated to the optimization and substantiation of BGD design parameters using various modeling methods.…”
Section: Introductionmentioning
confidence: 99%